Analisis Ketahanan Hidup Pasien Kanker Paru di RSUD Dr. Saiful Anwar - Pratiwi, Suryanti Dwi; Setyawan, Ungky Agus; Falyani, Silvy Amalia; Permatasari, Adinda Pramitra; Santosa, Andrew; Febriawati, Juwita; Prasetyo, Kevin Wahyudy; Yokanan (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Background: Comprising 14% of all cancer, lung cancer is the main cause of cancer-related mortality worldwide. Previous studies showed various findings regarding the survival rate of lung cancer, and factors significantly correlated with survival rate in lung cancer patients. Aim: This research aims to identify the profile and survival rate of lung cancer patients receiving chemotherapy in Saiful Anwar General Hospital from 2018 to 2020. Methods: This cohort retrospective study used medical records of patients diagnosed with lung cancer who underwent chemotherapy from 2018 to 2020. Data analysis was done using the Mantel Cox log rank test. Survival data shown as progression free survival (PFS) and overall survival (OS) were shown using Kaplan-Meier curves. Results: Subjects were largely male (73,2%). Adenocarcinoma is the most often type of lung cancer found (59,8%) with wild type EGFR mutation being the most prevalent (20,6%). Carboplatin – Paclitaxel is the most widely used chemotherapy regimen (54,6%). Survival analysis showed a significant correlation between age, OS, and PFS (p < 0,05) Conclusion: Various factors such as gender, cancer cell type, EGFR mutation, and chemotherapy regimen were not found to be related to survival rate in lung cancer patients. A significant correlation between age and survival rate showed potential in utilizing age as a predictor of survival rate in lung cancer patients.